Clozapine in Treatment-Resistant Bipolar Disorder With Suicidality. Three Case Reports - Wilkowska, Alina; Wiglusz, Mariusz S.; Cubała, Wiesław J. (Frontiers in Psychiatry, 2019)
Bipolar disorder is associated with a high risk of suicide attempts and suicide deaths. The suicide mortality of people with bipolar disorder is approximately 25 times higher than the general population. No approved pharmacological strategies for suicidality in bipolar disorder have been introduced so far. Clozapine is potentially a good candidate. This case series represents 3 treatment-resistant bipolar patients with severe suicidality who responded to low dose clozapine treatment.